Pre-resuscitation Lactate and Hospital Mortality in Prehospital Patients. (3rd July 2014) - Tobias, Adam Z.; Guyette, Francis X.; Seymour, Christopher W.; Suffoletto, Brian P.; Martin-Gill, Christian; Quintero, Jorge; Kristan, Jeffrey; Callaway, Clifton W.; Yealy, Donald M.
Abstract Objective. Serum lactate elevations are associated with morbidity and mortality in trauma patients, but their value in prehospital medical patients prior to resuscitation is unknown. We sought to assess the distribution of blood lactate concentrations prior to intravenous (IV) resuscitation and examine the association of elevation on in-hospital death. Methods. A convenience sample of adult patients over 14 months who received an IV line by eight EMS agencies in Western Pennsylvania had lactate measurement prior to any IV treatment. We assessed the lactate values and any relationship between these and hospital mortality (our primary outcome) and admission to the intensive care unit (ICU). We also compared the ability of lactate to discriminate outcomes with a prehospital critical illness score using age, Glasgow Coma Score, and initial vital signs. Results. We included 673 patients, among whom 71 (11%) were admitted to the ICU and 21 (3.1%) died in-hospital. Elevated lactate (≥2 mmol/L) occurred in 307 (46%) patients and was strongly associated with hospital death after adjustment for known covariates (odds ratio = 3.57, 95% confidence interval [CI]: 1.10, 11.6). Lactate ≥2 mmol/L had a modest sensitivity (76%) and specificity (55%), and discrimination for hospital death (area under the curve [AUC] = 0.66, 95%CI: 0.56, 0.75). Compared to the prehospital critical illness score alone (AUC = 0.69, 95% CI: 0.59, 0.80), adding lactate to the score offered modest improvement (net reclassification improvement = 0.63, 95%CI: 0.23, 1.01, p < 0.05). Conclusions. Initial lactate concentration in our prehospital medical patient population was associated with hospital mortality. However, it is a modest predictor of outcome, offering similar discrimination to a prehospital critical illness score.